Epidural Anaesthesia Saved A Patient With Multiple Co-Morbid Condition - Khatun, Rahena; Ali, Md Zulfikar (KYAMC Journal, 2017)
Epidural anaesthesia has been routinely used for many years and widely accepted as an effective mathod of pain relief . The procedure is commonly performed as a sole anaesthesic or in combination with spinal or general anaesthesia. In our case Md. Alauddin, 59 years old male was admitted in KYAMCH with complaints of diabetic gangrene of right foot with features of septicemia and he has a long history uncontrolled diabetes mellitus and hypertension leading to developed ischemia heart disease and CRF. After proper evaluation patient's physical status was graded as ASA (American society of Anesthesiologists) class-IV, and selected for above knee amputation of right lower limb but patient was unfit for anesthesia due to his co morbid conditions. As a life saving procedure the operation was done under epidural anesthesia and per- operative and postoperative recovery was uneventful. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 729-730